2016
DOI: 10.1002/hep.28676
|View full text |Cite
|
Sign up to set email alerts
|

Receptor interacting protein 3 protects mice from high‐fat diet‐induced liver injury

Abstract: Multiple pathways of programmed cell death are important in liver homeostasis. Hepatocyte death is associated with progression of nonalcoholic fatty liver disease (NAFLD) and inhibition of apoptosis partially protects against liver injury in response to high fat diets (HFD). However, the contribution of necroptosis, a caspase-independent pathway of cell death, to HFD-induced liver injury is not known. Wild-type C57BL/6 and receptor interacting protein (RIP) 3−/− mice were randomized to chow or HFD. HFD-fed C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 34 publications
(85 reference statements)
3
135
2
1
Order By: Relevance
“…This has led researchers to consider other types of cell death [123125]. Treatment with palmitic acid induces not only apoptosis, but also an emerging type of cell death termed necroptosis [123, 124].…”
Section: Die Another Way? Caspase-independent Death Signals and Nashmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led researchers to consider other types of cell death [123125]. Treatment with palmitic acid induces not only apoptosis, but also an emerging type of cell death termed necroptosis [123, 124].…”
Section: Die Another Way? Caspase-independent Death Signals and Nashmentioning
confidence: 99%
“…However, recent functional studies with RIP3 knockout mice have provided controversial results. Although RIP3 knockout mice were protected from NASH induced by an MCD diet [123, 124], HFD-induced liver injury and steatosis were exacerbated in RIP3-deficient mice [125]. Although both diets induce similar pathological features, their pathogenic mechanisms are quite distinct.…”
Section: Die Another Way? Caspase-independent Death Signals and Nashmentioning
confidence: 99%
“…[1][2][3] Lately, high-fat diet (HFD)-induced inflammatory responses in the peripheral tissues, especially in liver, cardiac muscle, and kidney, have been well characterized. [4][5][6] In a previous research, HFD was found to be capable of causing 3 CKD, a progressive loss in renal function over a period of months or years, has been regarded as a threat to people all over the world. 7,8 As the final manifestation of CKD, renal fibrosis is a common pathway toward kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…The latter result is intriguing, as RIPK3, the only identified kinase capable of activating MLKL, is not detectable in normal hepatocytes (8,13). RIPK3 induction has been suggested to occur in chronic liver injury, such as alcoholic and nonalcoholic steatohepatitis; however, actual necroptosis due to putative induction of RIPK3 in the liver has not been convincingly demonstrated (14)(15)(16). Hepatocytes do express MLKL, though at lower levels than nonparenchymal cells, making MLKL-induced cell death a possibility (8).…”
Section: What Pathway Killed the Hepatocyte?mentioning
confidence: 99%